Análise citogenética de espécies e híbridos interespecíficos de Paspalum L. (Poaceae) - Costa, Nicolle Vieira Santos (Universidade Federal de São Carlos, 2023)
The genus Paspalum L. (Poaceae) comprises about 350 species, many of which are characterized by high forage potential. The genus presents predominantly polyploid apomictic and diploid sexual species. For breeding programs, identifying the meiotic behavior of the species is essential to direct the crossings, being the objective of this work to characterize the meiotic behavior of species and hybrids of Paspalum arising from interspecific crossings. Seven accessions of five species were selected: BGP 149 (P. rojasii Hack), BGP 210 and 337 (P. maritimum Trind.), BGP 289 and 486 (P. malacophyllum Trin.), BGP 401 (P. conjugatum P. J. Bergius) , BGP 436 (P. dilatatum Poir.) and seven hybrid plants: Plant 2, 37, 77, 89, 206, 285, 298, for chromosome count and meiotic behavior analysis. All accessions were considered tetraploid with 40 chromosomes, showing some genotypes with regular meiotic behavior (BGP 210, BGP 337, BGP 289, BGP 486) and others with irregular behavior (BGP 149, BGP 401). In accession BGP 436, it was not possible to affirm ploidy. Among the hybrid plants, plants 2, 37 and 285 are diploid, accounting for 20 chromosomes, with regular meiotic behavior. Plants 89, 206 and 298 showed tetraploidy and irregular meiotic behavior, diverging from plant 77 which showed tetraploidy and regular meiosis. The results obtained in the present work contribute to confirm and review the ploidy and meiotic behavior of different species belonging to the genus Paspalum L. with predominance of polyplody. In addition, the possibility of interspecific crossing within the genus Paspalum and obtaining fertile hybrids, with meiotic regularity demonstrated in the work, opens up the possibility of its use within breeding programs.
Cytogenetic analysis of interspecific species and hybrids from Paspalum L. (Poaceae)
Keywords: Paspalum; Citogenética; Cromossomos; Melhoramento genético; CIENCIAS BIOLOGICAS::GENETICA